Analysis of student learning obstacles in exponential materials: exploratory case study - Dewi, Aprianah Puspa Sari; Zaini, Muhammad; Rizal, Muhammad; Safitri, Widya Sani (Nashir Al-Kutub Indonesia, 2023)
Exponential learning that had been occurring so far did not pay attention to the learning obstacles that students experienced. In general, the teacher delivered material by referring to documents, textbooks, or reference books. Therefore, it was important to conduct a study that examined learning obstacles in exponential material. The purpose of this research was to analyze the learning barriers associated with exponential material. The method used in this study was descriptive qualitative, using data collection techniques in the form of observation, tests, interviews, and documentation. The research subjects were 30 students of Mts NW Aik Anyar class VIII D. Data retrieval in the research was based on the results of student answer tests using the exponential question instrument consisting of five items. The results showed that there were still many students who had difficulty working on exponential questions. It was concluded that student learning barriers were divided into two factors: ontogeny barriers (learning readiness) and epistemological barriers (knowledge of students with limited application contexts).